Perceived Impact of Online Public Access Catalogue (OPAC) On effective retrieval of information resources by postgraduate students in Benue State University, Makurdi - Tofi Simon Ternenge; Tarbo Nguwasen Dorcas; Agor Cornelius Terwase; Tyopev Comfort Member (Newinera Publisher, 2020)
ABSTRACT The study investigated the perceived impact of OPAC on effective retrieval of information resources by postgraduate students in Benue State University, Makurdi. The study looked at the perceived impact of OPAC on effective retrieval of information resources, purpose of utilizing OPAC by postgraduate students, search strategies used by postgraduate students for effective retrieval of information resources, challenges as well as strategies to enhance the use of OPAC by postgraduate student for effective retrieval of resources. Five (5) objectives with corresponding research questions guided the study. The study adopted descriptive survey research design. The population of the study was made up of 38 postgraduate students who are registered with Benue State University Library. However, the census sampling was adopted for the study due to the small nature of the population. The instrument for data collection was self-structured questionnaire titled “Perceived Impact of OPAC on Information Retrieval Questionnaire” (PIOPACIRQ) which was validated by experts and a reliability coefficient of 0.947 was obtained. Data was collected and analyzed using frequent count and means. Findings of the study revealed that, there is a high perceived impact of OPAC on effective retrieval of information resources by postgraduate students in Benue State University, Makurdi. Finding also revealed that, postgraduate students in Benue State University, Makurdi utilize OPAC for various purposes such as to know the available resources in the university library, to locate books by author, title and subject, assists in obtaining books from the university library, among others. Finding also revealed the search strategies used by postgraduate students for effective retrieval of information resources in Benue State University Makurdi to include by author, title, subject and edition. The study further revealed the challenges hindering the use of OPAC for effective retrieval of information resources in Benue State University, Makurdi to include: lack of skilled library professionals to assists students, lack of orientation from library staff, lack of time to retrieve the vast information, slow internet connectivity speed, among others. Findings finally revealed some key strategies to enhance the use of OPAC for effective retrieval of information resources by postgraduate students in Benue State University, Makurdi which include: employment of skilled/competent library staff, need to design user-friendly OPAC template, improvement of internet connectivity speed, and organizing user education program to orientate postgraduate students on the use of OPAC, among others. Recommendations were also made based on the findings of the study.